Effect of Corporate Governance on Increasing Foreign Direct Investment in Saudi Arabia (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2024)
This research paper aimed to investigate the relationship between corporate governance and foreign direct investment (FDI) in the Kingdom of Saudi Arabia.  It examined various aspects of corporate governance such as executive compensation, financial reporting, board composition and the shareholder rights. It analyzed the trends, patterns and factors that may affect the decisions of foreign direct investors. The findings revealed that the Kingdom of Saudi Arabia has conducted a great progress in the field of utilizing corporate governance on increasing the foreign direct investments; however, there is a need for improving the quality. The study also provided some recommendations to create more stable environment to support FDI adequately as well as utilizing adequate corporate governance practices such as strengthening the independent board oversight and enhancing the rights of shareholders are among these factors. Improving the executive compensation practices and adopting international financial reporting can increase the number of investments as well as there will be coherence between the economic regulations in the Kingdom and those of other countries. Increasing the corporate social responsibility as well as strengthening the regulatory framework to facilitate applying corporate governance measures as well as enhancing foreign direct investments are recommended as well. Fostering the culture of good governance and providing facilities to attract foreign investments are suggested along with asserting the importance of enhancing the international cooperations.